Literature Review : Potensi Tanaman Mawar Merah (Rosa damascena) Beserta Kandungan Senyawa di Dalamnya - Imran, Ali (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Processing of plants as medicine or as industrial products is mostly done nowadays, for example in the beauty industry. Rossa damascena is a plant that can be used as a medicinal plant. This flower has many benefits, its essential oil and extract have long been used in body wash products, perfumes, skin lotions and medicines. However, there is not much management and distribution of drugs circulating in the community. The processing of these medicinal plants is a promising matter for pharmacists, because utilizing medicinal plants to be used as medicine can expand the nomenclature of drugs. The method used is the collection and screening of data that has inclusion and exclusion criteria. The results obtained are various information regarding the compound content and its potency contained in Rosa damascena.